Researching graduate employability and graduate employability skills of non-traditional graduates in Nigeria - Sodeinde, Mojisola (University of the Witwatersrand, Johannesburg, 2024)
The outbreak of the coronavirus disease in 2019 (COVID-19) resulted in the global adoption of strict lockdown protocols implemented to curtail the proliferation of the virus. The Internet emerged as a leading tool for working remotely, e-teaching, online collaboration, gaming, and for video streaming and conferencing. This study aimed to investigate Nigerian employers' perceptions of hiring graduates who received their degrees from non-traditional modes of learning such as e-learning. The global pandemic became a transformational experience that opened the guardrails for innovative ideas on education and instruction, helping to accelerate the use of distance and virtual instructional tools at educational institutions such as universities during the lockdown. COVID-19 has thus changed how people work, teach, and learn worldwide. The over-arching question of this research was: What understanding do employers have of graduate employability and employability skills, and how does the degree delivery mode factor into recruitment decisions in Nigeria? Furthermore, the subsequent sub- questions were formulated to guide the research process: (1) What perceptions do employers have of graduates who obtained their qualification through alternative modes of learning such as online or e-learning? (2) How does the course delivery mode affect employers’ understanding of graduate employability, and employability skills in the Nigerian labour market? (3) What do employers of labour in Nigeria consider as key factors, with respect to competencies of e-learning and traditional classroom graduates, in recruitment decisions? (4) Using the USEM model of employability as an employability framework, how do the four key descriptors measure within the Nigerian labour market? Explanatory sequential mixed methods were utilized in this doctoral research, collecting quantitative data from one hundred and ten (110) Nigerian human resource professionals and collected qualitative data in semi-structured interviews from five (5) human resource professionals. The doctoral study found that Nigerian employers are more concerned with the personal attributes of graduates than they are with the delivery mode for instruction and learning in the academic institution of the graduate. While employers overwhelmingly view e-learning as comparative to the traditional mode of instruction and thus agree that there is tangible difference between the two modes, about half of all employers prefer to recruit graduates from a traditional on-campus mode of learning. iv Using USEM as the conceptual framework for employability and employability skills, personal attributes emerged as the most desirable set of skills for Nigerian employers, more important than subject matter knowledge. The consensus among employers indicates that there is no discernible distinction in the educational achievements between graduates who have completed their academic pursuits through conventional means and those who have opted for the virtual modality.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; GRADUATE EMPLOYABILITY; GRADUATE EMPLOYABILITY SKILLS; GRADUATES IN NIGERIA; SDG-4: Quality education; SDG-8: Decent work and economic growth